Studies on Deprotection of Cysteine and Selenocysteine Side-Chain Protecting Groups() - Harris, Katharine M. (2007)
We present here a simple method for deprotecting p-methoxybenzyl groups and acetamidomethyl groups from the side-chains of cysteine and selenocysteine. This method uses the highly elecrophilic, aromatic disulfides 2,2′-dithiobis(5-nitropyridine) (DTNP) and 2,2′-dithiodipyridine (DTP) dissolved in TFA to effect removal of these heretofore difficult to remove protecting groups. The dissolution of these reagents in TFA in fact serves to “activate” them for the deprotection reaction because protonation of the nitrogen atom of the pyridine ring makes the disulfide bond more electrophilic. Thus these reagents can be added to any standard cleavage cocktail used in peptide synthesis. The p-methoxybenzyl group of selenocysteine is easily removed by DTNP. Only sub-stoichiometric amounts of DTNP are required to cause full removal of the p-methoxybenzyl group, with as little as 0.2 equivalents necessary to effect 70% removal of the protecting group. The ability to remove the p-methoxybenzyl group from cysteine using DTNP required 2 equivalents of DTNP and the addition of thioanisole for complete deprotection. Thioanisole was absolutely required for the reaction in the case of the sulfur-containing amino acids, while it was not required for selenocysteine. The results are consistent with thioanisole acting as a catalyst. The acetamidomethyl group of cysteine can also be removed using DTNP, but required the addition of > 15 equivalents to be effective. DTP was less robust as a deprotection reagent. We also demonstrate that this chemistry can be used in a simultaneous cyclization/deprotection reaction between selenocysteine and cysteine residues protected by p-methoxybenzyl groups to form a selenylsulfide bond, demonstrating future high utility of the deprotection method.